Analysis of health aspects of students in two municipal schools in the Region Médio Sertão Alagoano - Machado, João Paulo (Pubvet, 2021)
The school is an institution of great influence in the formation of an individual, it also monitors the needs of the health situation through programs aimed at orienting and analyzing the well-being of students. The aim of this study was to analyze health aspects of students from two 9th grade classes located in two municipalities in the middle of the Alagoas backlands. This is a cross-sectional descriptive epidemiological study carried out in two public schools, using a questionnaire used previously in the Pesquisa Nacional de Saúde do Escolar (PeNSE). 71 students participated in this study, totaling 62% female, 36.6% male and 1.4% who did not identify themselves. Regarding food, it was observed that most students consume beans every day and 36.6% do not consume school meals. Regarding the use of cigarettes, alcohol and illicit drugs, it was found that the majority 73.24% had already tried some alcoholic drink and 9.96% had already smoked. Regarding their sexual and reproductive health, only 26.8% answered that they had already had sexual intercourse. Thus, it is necessary to take health actions in the schools studied, mainly related to the consumption of alcoholic beverages, sexual orientation and healthy eating, as education and awareness play an extremely important role in the dissemination of healthy habits.
Keywords: Health education; PeNSE; quality of life